Hemolytic assay for Huangqi Injection - Xiao, Hang; Xu, Yu-bin; Liu, Xia; Dou, De-qiang (Chinese herbal medicines, 2016)
Objective Huangqi Injection is a preparation with an extract of Astragali Radix which has a long history of being used as a tonic to strengthen the body＇s immunity. Anaphylaxis and hemolysis are two main adverse drug reaction （ADR） of injections. Our study was aimed to establish an approach for the （ADR） prediagnosis of Huangqi Injection. Methods An in vitro model for anaphylactoid assay of Huangqi Injection based on the release rate of histamine and 13-hexosaminidase of RBL-2H3 cells induced by injections and a colorimetric method based on the detection of hemoglobin resulted in the erythrocyte hemolysis for prediagnostic assaying the hemolytic ADR of injections were established. Results Both histamine and ~-hexosaminidase are the anaphylactiod mediators, but 13-hexosaminidase release induced by Huangqi Injection could not be determined by spectrophotometry due to the interference of the injection itself. In addition, normal hemolysis and abnormal hemolysis were discovered during the experiment. The fingerprints and tannins in different batches of injections showed obvious differences, indicating that the content of tannins was related to abnormal hemolysis and higher histamine-secreting from RBL-2H3 cells. Conclusion The results indicate that the hemolytic assaying method is not only suitable for prediagnostic assaying of hemolytic ADR of herbal medicine injection, but also partly reflects the anaphylaxis of herbal injections, and tannins may be the major factors causing abnormal hemolysis.